ANALYSIS ON THE SUSTAINABILITY OF EXTERNAL DEBT AND THE FINANCIAL VULNERABILITY OF THE TURKISH ECONOMY: 1989-2019 (Third Sector Social Economic Review, 2020)
The aim of this article is to analyze the sustainability of external debt in the Turkish economy between 1989-2019 with the help of indicators taken into account by the World Bank and to determine the level of financial vulnerability of the Turkish economy. In this context, 13 basic macro economic variables were selected for the Turkish economy and three different Financial Vulnerability Indexes (FVI) were derived. These indexes (FVI), the threshold-value of which is 0.35, were successful in predicting both the 1994 and 2001 currency crises for it has produced strong signals in the years immediately preceding the two “home-made” crises. However, none of the three different indexes value produced a signal predicting the 2008-2009 crises. But considering the fact that the said crises was “imported” and not “home-made”, this is neither surprising nor can be construed as a failure to predict. However, rapid increases in external debt in the 2010s led to FVI once again passing the threshold-value in 2017.  As a result, exports are the best way for Turkey, which has shown a weak outlook in recent years in terms of sustainability of external debt, to solve this problem.
Keywords: Sustainability of External Debt; Financial Vulnerability Index; Export